Adaptive neuro-fuzzy inference system-genetic algorithm vs . response surface methodology: a case of ferric sulfate-catalyzed esterification of palm kernel oil - Ishola, Niyi B.; Adeyemi, Omowumi O.; Adesina, Ayo Joshua; Odude, Victoria.O (Process Safety and Environmental Protection, 2020)
Process Safety and Environmental Protection